Peningkatan Keaktifan Siswa melalui pembelajaran Quantum Teaching di Sekolah Dasar - Akif Khilmiyah (At-Tarbawi 2011, 2010)
Peningkatan Keaktifan Siswa melalui pembelajaran Quantum Teaching di Sekolah Dasar